PENGARUH BRAIN GYM TERHADAP KEMAMPUAN KOGNITIF MEMORI JANGKA PENDEK PADA ANAK TUNA GRAHITA DI SLB NEGERI TANAH BUMBU - Bayu Purnama Atmaja; Rani Fitriani Arifin; Ritna Udiyani (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
The American Association on Mental Deficiency (AAMD) (2016) is mental retardation or mental disability as a disorder that includes general intellectual functions below the average (IQ 84 and below) based on individual tests that appear before the age of 16 years and show obstacles in adaptive behavior. Educational learning in Special Schools (SLB) still does not apply stimulation to the brain even though continuous brain stimulation can improve cognitive function because the brain has dynamic properties where brain plasticity can develop according to the stimulus provided by its environment (Sumaryanti, 2012). The American Occupational Therapy Association (Sujarwanto, 2015) suggests occupational therapy is a combination of art and science that is used to help and maintain health, overcome disabilities, analyze behavior, provide training and train patients suffering from physical, mental and social functioning disorders. The purpose of this study was to look at the effect of brain gym on short-term cognitive memory in mentally retarded children. This study is a type of Quasy Experiment research using one group pre-test post-test design research design. The sample in this study were mentally disabled children aged less than 12 years. The number of samples in this study were 11 respondents who were treated for 7 consecutive days. Test analysis using paired test. The results showed that brain exercise in mentally disabled children can improve cognitive abilities of short-term memory. The conclusion from this study there is the effect of brain gym on the cognitive abilities of short-term memory in mentally disabled children. Suggestions based on the results of this study are expected to enable Special School education to implement a brain gym before carrying out learning activities.